'It's our pleasure, we count cars here': an exploration of the 'neighbourhood-based connections' for people living alone with dementia. Issue 3 (30th March 2021) - Odzakovic, Elzana; Kullberg, Agneta; Hellström, Ingrid; Clark, Andrew; Campbell, Sarah; Manji, Kainde; Rummery, Kirstein; Keady, John; Ward, Richard
Abstract: The extent of social isolation experienced by people living with dementia who reside in the community has been well acknowledged, yet little is known about how people living alone with dementia maintain neighbourhood-based connections. The purpose of this study is to examine the experiences of people with dementia who live alone, focusing upon how they establish social networks and relationships in a neighbourhood context, and how they are supported to maintain this social context within everyday life. Multiple data collection methods were used including, semi-structured interviews, walking interviews, guided home tours and social network mapping, which were conducted with 14 community-dwelling people living alone with dementia (11 women and three men) situated across the three international study sites in England, Scotland and Sweden. Data were analysed using thematic analysis. The analysis revealed four main themes: (a) making the effort to stay connected; (b) befriending by organisations and facilitated friendships; (c) the quiet neighbourhood atmosphere; and (d) changing social connections. The analysis suggests that people with dementia who live alone were active agents who took control to find and maintain relationships and social networks in the neighbourhood. Our findings indicate the need to raise awareness about this specific group in both policy and practice, and to find creative ways to help people connect through everyday activities and by spontaneous encounters in the neighbourhood.